ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPEMIMPINAN TRANSAKSIONAL TERHADAP KEPUASAN KERJA ASISTEN APOTEKER DI RUMAH SAKIT BUDI KEMULIAAN BATAM - Aznedra, Aznedra (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
This study aimed to analyze the influence of leadership style on job satisfaction, by measuring the effect of transformational leadership style and transactional leadership to satisfaction of job satisfaction. Is there a positive and significant effect of leadership style collected koesioner methods, namely multi-factor leadership questionnaire (MLQ) to gauge perceptions of job satisfaction. The study population was an assistant pharmacist at Hospital Budi Glory Batam. The total sample of 80 respondents were taken by proportional random sampling technique. Method is a qualitative and quantitative analysis. Quantitative analysis was performed by using multiple regrsi test to test the hypothesis set at 5% level.               Based on these results the following regression equation: Y = 55.111 to 0.051 X1 - X2 0.098 + 0.936 X3 of the equation known transformational leadership style and transactional leadership has a positive and significant effect on job satisfaction with a different influence. Transformational leadership has a greater influence on job satisfaction compared to transactional leadership.  Keywords: Transformational leadership, transactional leadership, job satisfaction